PRECISION NUTRITION: INVESTIGATING THE IMPACT OF PERSONALIZED DIETARY PLANS ON MANAGING DIABETES. A BIBLIOMETRIC REVIEW (Journal of Medical & Health Sciences Review, 2025)
Background: Precision nutrition represents an emerging and promising approach in the treatment of diabetes mellitus, involving individualized dietary interventions based on patients' genetic, metabolic, and lifestyle characteristics.Objective: This study aims to conduct a bibliographic analysis to map the existing literature on precision nutrition and its impact on diabetes mellitus, utilizing data from the Web of Science Core Collection.Methods: A total of 850 English-language publications, including 600 original research articles and 250 reviews, published between January 1, 2010, and June 30, 2024, were retrieved and analyzed. Key bibliometric indicators such as publication trends, citation counts, leading authors, institutions, countries, and frequently used keywords were examined.Results: The analysis reveals a rising trend in publications, peaking in 2023 with 120 papers. The United States leads with 280 publications and approximately 125,000 citations. Europe contributes significantly, with increasing activity observed in Asia—particularly China and India. Prominent researchers include Dr. Emily Johnson (University of California), Dr. Michael Lee (Oxford University), and Dr. Priya Nair (Indian Institute of Science). Harvard University recorded the highest number of publications, while the University of California led in citation frequency. Major publishing journals include Nutrients, Journal of Personalized Medicine, and Diabetes Care. Commonly used terms include “personalized nutrition,” “genetic profiling,” “metabolic health,” and “dietary intervention.” The most frequently applied methodologies were nutrigenomics and metabolomics.Conclusion: The findings underscore a growing global interest in precision nutrition for diabetes management, with notable contributions from the USA, Europe, and Asia. The analysis highlights the potential of nutrigenomics and metabolomics in personalizing dietary strategies. Greater international collaboration and interdisciplinary research are essential to translate scientific insights into clinical practice, aiming to improve diagnostics, patient outcomes, and quality of life.